The risk of pulmonary tuberculosis in underground copper miners in Zambia exposed to respirable silica: a cross-sectional study - Kingsley Ngosa; Rajen N. Naidoo (BMC, 2016)
Abstract Background Pulmonary tuberculosis (PTB) among underground miners exposed to silica remains a global problem. Although well described in gold and coal mining, risk in other mining entities are not as well documented. This study aims to determine dust-related dose response risk for PTB among underground miners exposed to silica dust in Zambia's copper mines. Methods A cross sectional study of in-service miners (n = 357) was conducted at Occupational Health and Safety Institute (OHSI), Zambia. A systematic review of medical data over a 5-year period from assessments conducted by doctors at OHSI and statutory silica exposure data (n = 16678) from the Mine Safety Department (MSD) were analysed. Lifetime cumulative exposure metrics were calculated. Multivariate logistic regression analysis was used to determine the association between PTB and lifetime exposure to silica, while adjusting for various confounders. Results The median respirable silica dust level was 0.3 mg/m3 (range 0.1-1.3). The overall prevalence of PTB was 9.5 % (n = 34). High cumulative respirable silica dust category showed a statistically significant association with PTB (OR = 6.4 (95 % CI 1. 8-23)) and a significant trend of increasing disease prevalence with increasing cumulative respirable silica dust categories was observed (ptrend < 0.01). Smoking showed a statistically significant association with PTB with OR = 4.3 (95 % CI 1.9-9.9). Conclusions Our results demonstrate the association of increased risk for certified active TB with cumulative respirable dust in a dose related manner among this sample of copper miners. There is need to intensify dust control measures and incorporate anti-smoking interventions into TB prevention and control programmes in the mines.